Shot put kinematics of world class athletes with an intellectual disability - Willwacher, S.; Potthast, W.; Müller, R.; Brüggemann, G. P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to identify basic kinematics differences in shot put kinematics between athletes with an intellectual disability (ID athletes) and able minded athletes. Data collection took place at the 2010 INAS athletics world indoor championships for athletes with an intellectual disability. Four high speed (100Hz) video cameras were utilized to observe 3D kinematics of the shot using the DLT method. The performance of ID athletes observed in this study was much lower compared to the performance of world class able minded athletes described in the literature. An analysis of basic kinematic characteristics of the gliding technique of the ID athletes revealed that they use a reduced acceleration path to release the shot, leading to a reduced speed of release.